Is unstable surface training advisable for healthy adults? - Hubbard, D. (Strength and Conditioning Journal, 2010)
UNSTABLE SURFACE TRAINING HAS BECOME POPULAR AMONG HEALTHY ADULTS AND PERSONAL TRAINERS WORKING WITH HEALTHY ADULTS. ALTHOUGH UNSTABLE SURFACE TRAINING HAS BEEN SHOWN TO INCREASE CORE MUSCLE ACTIVITY AND STABILITY, ITS APPLICATION IS STILL VERY LIMITED. UNSTABLE SURFACE TRAINING DECREASES FORCE OUTPUT OF LIMB MUSCLES, ALTERS NEUROMUSCULAR RECRUITMENT PATTERNS, AND CAN INTERFERE WITH STABLE SURFACE TRAINING ADAPTATIONS. SPECIFICITY OF TRAINING SHOULD BE CONSIDERED, AND IF UNSTABLE SURFACE TRAINING IS USED, IT SHOULD BE DONE APPROPRIATELY.